Presence of Interferon-Gamma and IL-2 in Supernatants of Salmonella enteritidis-Immune Lymphokines - G-Verduzco, Gabriela V.; Tellez, Guillermo; Kogut, Michael H.; Isibasi, Armando; Ortiz-Navarrete, Vianney (International Journal of Poultry Science, 2009)
Investigations in our laboratories have indicated that an increased resistance to Salmonella enteritidis SE organ infectivity in chickens was conferred by the immunoprophylactic administration of SE-immune lymphokines (SE-ILK). Resistance has been associated with an enhanced heterophilic accumulation within 4 h of ILK injection. Further studies demonstrated that CxCLi2 is produced locally by the host in response to both the SE infection and the SE-ILK suggesting that IL-8 is a major chemotactic factor produced by the host, which aids in mediating the SE-ILK induced recruitment of heterophils to the site of SE invasion. In the present study, two bio-assays confirmed the presence of IFN and IL-2 functions in SE-ILK that may also participate in the establishment of the reported protection against Salmonella infections. The IL-2 and IFN effects detected in this work suggest that bird’s immune response develops similarly to that of mammals, with some features corresponding to the species.